2012
DOI: 10.1186/1471-2458-12-399
|View full text |Cite
|
Sign up to set email alerts
|

Problem drinking and physical intimate partner violence against women: evidence from a national survey in Uganda

Abstract: Background Problem drinking has been identified as a major risk factor for physical intimate partner violence (PIPV) in many studies. However, few studies have been carried on the subject in developing countries and even fewer have a nationwide perspective. This paper assesses the patterns and levels of PIPV against women and its association with problem drinking of their sexual partners in a nationwide survey in Uganda. Methods The data came from the women’s dataset in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
59
5
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 32 publications
(46 reference statements)
12
59
5
3
Order By: Relevance
“…Our analysis replicates prior research showing that completing higher education tends to have a protective effect on IPV risk, such that – compared to women with higher education, women with secondary level education had a six-fold increase and almost three-fold increase in the frequency of physical and sexual IPV, respectively (Abramsky et al, 2011; Tumwesigye, Kyomuhendo, Greenfield, & Wanyenze, 2012). This suggests that educated women may be less likely to accept traditional gender roles and could be more vocal in their response to violence by their husbands.…”
Section: Discussionsupporting
confidence: 85%
“…Our analysis replicates prior research showing that completing higher education tends to have a protective effect on IPV risk, such that – compared to women with higher education, women with secondary level education had a six-fold increase and almost three-fold increase in the frequency of physical and sexual IPV, respectively (Abramsky et al, 2011; Tumwesigye, Kyomuhendo, Greenfield, & Wanyenze, 2012). This suggests that educated women may be less likely to accept traditional gender roles and could be more vocal in their response to violence by their husbands.…”
Section: Discussionsupporting
confidence: 85%
“…Tumwesigye and colleagues [27] investigated IPV victimization among women in Uganda and found socioeconomic status including education, employment status, income, and education level as well as the employment status of the partner to be potential risk factors. Furthermore, Lemon and colleagues [28] reported that current smoking and frequent alcohol use are related to IPV victimization among women living in the US (Rhode Island).…”
Section: Introductionmentioning
confidence: 99%
“…This has placed these countries within the group of high-consumption countries (see for example World Health Organization [WHO], 2004;WHO, 2014). As a result, research on alcohol consumption and related harm have received considerable attention in both Nigeria and Uganda (e.g., Esan, Makanjuola, Oladeji, & Gureje (2013) ;Gureje, 1999;Gureje et al, 2007;Kobusingye, Guwatudde, & Lett, 2001;Obot, 2012;Obot, Wagner, & Anthony, 2001;Ohaeri & Odejide, 1993;Ovuga & Madrama, 2006;Swahn, Palmier, & Kasirye, 2013;Tumwesigye & Kasirye, 2005;Tumwesigye, Kyomuhendo, Greenfield, & Wanyenze, 2012;Zablotska et al, 2009). …”
Section: Introductionmentioning
confidence: 99%